Теоретичне осмислення етапів формування філософії та естетики українського літературного імпресіонізму: від початків до організаційного розгрому - Ямчук, Павло; Yamchuk, Pavlo (Східноєвропейський національний університет імені Лесі Українки, 2014)
Досліджено світогляд та естетичні принципи вітчизняного літературного імпресіонізму. З’ясовано етапи його формування, окреслено їх сутність і вплив на нього загальноєвропейських домінант й української національної культури та соціально-історичних факторів . This article investigates the philosophical foundations and aesthetic principles of national literary impressionism. Explained the stages of its formation, outlined their essence and influence on him as a pan-European dominants and Ukrainian national culture and socio-historical factors. The article focuses on complex and extraordinary transformation processes impressionistic poetics and philosophy from the era of its formation in Nala 1890 and till enforced artificial defeat in the first half of the 1930s, studied retseptsionnoe field Ukrainian literary impressionism in the context of literary criticism and scientific reflections of the past and the present. Focuses on the actualization of the modern discourse of humanitarian ideas of scientists – the first researchers philosophy and aesthetics of Russian literary impressionism. Attention is paid to the analysis of complex inner world of heroes impressionistic prose, philosophical and positions of Ukrainian study its specificity and dominant features, the transcendental nature of the significant features of philosophy and poetics of impressionism.
Theoretical Understanding of the staGes of Formation of Philosophy and Aesthetics Ukrainian liteRARy Impressionism, From the Beginning to the Organizational defeat.
Keywords: світобачення; естетика; український літературний імпресіонізм; трансцендентальність; philosophy; aesthetics; Ukrainian literary impressionism; transcendence